Crafting the Personal Branding in Academic Contexts: A Qualitative Analysis of Student-Produced Autobiographical in Book Chapters Based on Contextual Learning - Suci Ramadhanti Febriani; Zainul Arifin; Torkis Lubis (Universitas Islam Negeri Palangka Raya, 2026)
The competence of writing narratives in Arabic requires mastery of developing complex ideas and linguistic structures. This qualitative study aims to analyze the responses, impacts, and challenges of implementing contextual learning through writing autobiographical narrative texts based on book chapter media for university students. The participants were 63 fifth-semester students of Arabic Language Education at Universitas Islam Negeri Imam Bonjol Padang. Data were collected through observation, book chapter document analysis, and qustionnaire, then analyzed thematically. The results revealed three main findings: first, contextualization of personal experiences increased self-efficacy and emotional engagement in the writing process; second, there was a significant increase in syntactic complexity and variation of Arabic sentence structures; third, book chapter media facilitated creative expression through experimentation with paragraph and visual design. However, challenges arose in aspects of grammatical accuracy and internalization of Arabic rhetorical rules. This study concludes that the book chapter-based contextual approach has the potential as an innovative pedagogical model that integrates writing skill development with linguistic identity formation. Further research with a mixed-methods design is recommended to quantitatively measure the model's effectiveness and explore its application in other language learning contexts.